EFFECTIVE CONTRACT AT THE UNIVERSITY AS A DRIVER OF WORK QUALITY IMPROVEMENT OF SCIENTIFIC AND PEDAGOGICAL WORKERS - I. E. Nikulina (Высшее образование в России)
This paper investigates the theory and practice of using effective contracts for academic staff. The study identifies the effects of the implementation of effective contracts at the National Research Tomsk Polytechnic University using bottom-up approach. Recently, the International Standards of Scientific and Educational Activities have significantly changed the programs for the development of universities. Therefore, in recent years, the system of effective contracts is actively developing. In this research SWOT-analysis of effective contract system is introduced. The described system is used for more than three years at the National Research Tomsk Polytechnic University. The first part of the research is devoted to the history of origin, principles and problems of applying effective contracts. In the second part of the article, recommendations are given for the introduction of a system of effective contracts. The Research goal was to study the theoretical and socio-economic aspects of the practice of applying effective contracts at the university to improve the motivation system and avoiding erroneous actions to manage the process of its development. The methodological basis of the study is the system and competence approaches to the management of quality of work of academic staff. The practical significance of the research consists in the presented recommendations on improving the process of introduction of the effective contract system for academic staff, contributing to the development of a competitive environment, and the formation of new mechanisms for motivating the idea of achieving a positive strategic effect in a university.